Border Development Model on the Human Development Aspects for Sustainable Community - Semuel Risal; Irawanto Irawanto; Putri Hergianasari; Anita Ade Rahma; Ika Devy Pramudiana (Jurnal Borneo Administrator, 2022)
The Indonesian government has implemented a border development policy. Still, it has not been able to answer the complexity of the problems that occur in border areas, especially in North Kalimantan. The development of border areas is closely related to the mission of national development, defence and state security to improve the Welfare of the people in the border areas, especially to ensure the integrity and sovereignty of the state. However, the condition of border communities in North Kalimantan is increasingly marginalized, where poverty and regional isolation trigger the high demands of local people to become border crossers to Malaysia. This study will examine the factors causing the economic backwardness of border communities in North Kalimantan, poverty and isolation of border communities, and security issues at the border. The results show that the border area needs to be closely monitored because it is a security-prone area. This makes the border development paradigm in Kaltara prioritize a security approach rather than Welfare. This causes the border areas in North Kalimantan to be scarcely touched by the dynamics of development. Therefore, border development needs to be placed in a people centre of development-oriented to people's economic development for sustainable communities through accelerating economic growth, improving the quality of human resources, and strengthening institutional capacity for border area development. Thus, border communities can enjoy prosperity by protecting and maintaining state sovereignty at the border.